Relationship between anemia in the first trimestre and low birth weight in four Maternal and Child Health Centers in Lima Sur during 2019 - Yovera-Aldana, Marlon (2021)
Objective: To determine the relationship between maternal anemia in the first trimester of pregnancy and low birth weight in four mother-and-child-health centers in Southern Lima during 2019. Material and methods: A retrospective cohort study from a secondary database was performed, where pregnant women from 4 middle-complexity Health Centers from Southern Lima were included. Deliveries took place during 2019, excluding preterm newborns. First trimester hemoglobin concentration <11 g/dL was defined as anemia and birth weight <2500 g was defined as low birth weight. Cumulative incidence for anemia was calculated, and relative risk (RR) adjusted for potential confounders was also calculated. Results: Two hundred and twenty one pregnant women were included. Seventy-six per cent were between 18 and 35 years old. Forty-two percent were primigravida, fifty-two percent had excess body weight, and sixty percent had six or more prenatal control visits. Nearly one quarter (23,5%) of all pregnant women had anemia during the first trimester, and there were 2,7% cases of low birth weight. Anemia during the first trimester of pregnancy increased 11 times the frequency of newborns with low birth weight, independently of age, body mass index, and parity (adjusted RR = 11,1; 95% CI: 1,3–97,2; p= 0,029). Conclusions: In the studied sample, one out of four pregnant women had anemia during the first trimester of pregnancy, increasing up to 11 times the cumulative incidence for having a neonate with low birth weight.